Collagen-derived dipeptide prolyl-hydroxyproline cooperates with Foxg1 to activate the PGC-1α promoter and induce brown adipocyte-like phenotype in rosiglitazone-treated C3H10T1/2 cells - Nomura, Kaho; Kimira, Yoshifumi; Kobayashi, Ryosuke; Shiobara, Yuna; Osawa, Yoshihiro; Kataoka-Matsushita, Aya; Shimizu, Jun; Wada, Masahiro; Mano, Hiroshi (Frontiers in Nutrition, 2024)
Background: The global obesity epidemic is a significant public health issue, often leading to metabolic disorders such as diabetes and cardiovascular diseases. Collagen peptides (CP) and their bioactive component, Prolyl-hydroxyproline (Pro-Hyp), have shown potential in reducing adipocyte size, with unclear mechanisms concerning brown adipocyte differentiation.Methods: We investigated the effects of Pro-Hyp on the differentiation of brown adipocytes in C3H10T1/2 mesenchymal stem cells, focusing on its impact on adipocyte size, gene expression related to brown fat function, and mitochondrial activity.Results: Pro-Hyp treatment decreased adipocyte size and upregulated brown fat-specific genes, including C/EBPα, PGC-1α, and UCP-1. Remarkably, it did not alter PPARγ expression. Pro-Hyp also elevated mitochondrial activity, suggesting enhanced brown adipocyte functionality. A Pro-Hyp responsive element was identified in the PGC-1α gene promoter, which facilitated the binding of the Foxg1 transcription factor, indicating a novel regulatory mechanism.Conclusion: Pro-Hyp promotes brown adipocyte differentiation, potentially offering a therapeutic strategy for obesity management. This study provides a molecular basis for the anti-obesity effects of CP, although further in vivo studies are needed to confirm these findings and to investigate the potential impact on beige adipocyte differentiation.